Food Policy in Recreation and Sport Facilities in Canada: Lessons Learned from Eat, Play, Live - Caswell, Marian Susan (University of Waterloo, 2025)
BACKGROUND The advent of voluntary nutrition guidelines for municipally funded recreation and sport facilities in three Canadian provinces presented the opportunity to evaluate both policy impact and implementation support approaches. The current research extended the Eat, Play, Live (EPL) trial which examined food environments within recreation and sport facilities in the three nutrition guideline provinces (British Columbia, Alberta, Nova Scotia), with and without a capacity-building intervention (CBI), and a non-guideline control province (Ontario). RESEARCH OBJECTIVES 1. Describe recreation and sport facility food environments in the absence of provincial nutrition guidelines. a. Assess the healthfulness of food and beverages offered for sale and vending sales within a convenience sample of recreation and sport facilities in Ontario, Canada and compare between the cohort with a municipal policy banning the sale of water in single-serve plastic water bottles in municipally funded facilities versus the cohort without such a policy. 2. Explore components of the CBI that had the greatest impact on the healthfulness of food environments within recreation and sport facilities in nutrition guideline provinces randomized to receive the EPL CBI. a. Examine the relationships among the implementation factors: guideline mobilization, facility context, and facility-level policy, and changes to the healthfulness of the food environment in facilities within nutrition guideline provinces randomized to receive the CBI; and b. Describe and frame relationships between and among CBI components and changes to the healthfulness of recreation and sport facility food environments using the updated Consolidated Framework for Implementation Research (CFIR) [1]. METHODS Study 1: Ontario Recreation and Sport Facility Food Environment Cross-sectional descriptive data on the food environments in municipal recreation and sport facilities in Ontario were collected on two occasions; time 1 (T1) and time 2 (T2), marking the start and end of the 18-month CBI. Differences in the healthfulness of food and beverages between facilities with and without a bottled water ban were measured using: a) Vending and concession packaged product profiles assessed by classifying healthfulness of each according to established British Columbia Ministry of Health Guidelines as Sell Most, Sell Sometimes, and Do Not Sell [2]; b) Concession food environments scoring as measured using the Nutrition Environment Measures Survey-Restaurant reduced item audit (rNEMS-R) Fast Casual and Fast Food Summary [3]; and c) Itemized sales data for vending products targeting a two-week period around facility audits. Descriptive statistics were calculated and differences between the two groups compared using Student’s two-sided t-test. Study 2: Guideline Implementation Factors and Changes in Facility Food Environment In facilities across three voluntary nutrition guideline provinces (British Columbia, Alberta, Nova Scotia) that had been randomized to the EPL 18-month CBI, a qualitative comparative analysis (QCA) examined relationships between implementation factors: guideline mobilization (Mobilization), facility context (Context), and facility-level policy (Policy), and positive (healthier) food environment changes. Regression analysis was also used to examine the strength of relationships between the implementation factors and changes to healthfulness. Implementation factor ratings (low [1], low-moderate [2], moderate [3], moderate-high [4], high [5]) from a cross-case analysis, with each facility acting as an independent case, were used to conduct both the QCA and regression analyses. Facility healthfulness was assessed as described for Study 1. For the QCA positive change was defined as a decrease in the proportion of Do Not Sell products for vending and concession packaged beverages and snacks and as an increase in score for rNEMS-R Fast Summary scores. The ratings for the implementation factors were based on indicators for guideline mobilization, (the number and intensity of CBI activities implemented, access and use CBI of resources), facility context (training/expertise, priorities, structural characteristics, partnerships, champion and staff changes) and facility-level policy (quality, status and breadth) that were extracted from a range of data sources: a) An implementation summary for each facility was created by EPL provincial coordinators which included the following documentation: a. Implementation plans documenting goals, tasks, responsibility, and timeline according to operational area (e.g., vending); b. Mobilization summaries documenting activities, intensity of activities and access and use of EPL resources; c. Context summaries documenting relevant context changes (e.g., food service contractor changes); d. Technical support provided; e. Regional teleconference minutes; f. Interview transcripts of intervention mid-point and end-point interview with facility representatives (CBI facility Leads); g. Provincial coordinator documentation around role and engagement of CBI facility Leads, buy-in, and major challenges and facilitators; h. A facility level policy assessment using purpose-built questions integrated in a self-assessment audit tool adapted to the recreation and sport facility context and available documents on facility-level policy or policies. Study 3: EPL CBI Multiple-case Evaluation Framed by CFIR A multi-case study approach was used to examine the impact and strategy variation of the CBI across different facility contexts. Two facilities who achieved greater success at increasing the healthfulness of the recreation and sport facility food environment (as a proxy for provincial nutrition guideline uptake/implementation) were compared and contrasted with two facilities that were less successful at effecting change. The updated CFIR [1] was used to frame the analysis. The selection of case facilities from the 17 receiving the CBI was based on facility rankings for nine food environment outcomes assessed through facility audits (as outlined for Study 1) at baseline (T1) and end-of-study (T2). RESULTS Study 1: Ontario Recreation and Sport Facility Food Environment Packaged snack and beverage offerings available in vending machines and at concessions were predominantly Do Not Sell and rNEMS-R scores were well below ideal across the 16 participating facilities. Packaged snacks ranged from 94-96% Do Not Sell in facilities that allowed the sale of bottled water (n=8) and similarly from 87-94% in facilities banning bottled water (n=8). Beverages ranged from 74-77% Do Not Sell in facilities that allowed the sale of bottled water and differed significantly (p<0.05) from the 87-88% Do Not Sell in facilities banning bottled water. rNEMS-R Fast Casual scores were similar at 6.1 and 7.1 for facilities allowing bottled water versus those banning its sale, compared to an ideal score of 48. Mirroring availability, sales from vending snacks and beverages were also predominantly Do Not Sell. Differences were found for beverage availability and sales between facilities in jurisdictions banning bottled water and those that allowed the sale of bottled water. The proportion of Do Not Sell beverages available was significantly (p<0.05) higher in the absence of bottled water (90% versus 79%) and the proportion of Sell Most (0% versus 14%) was significantly (p<0.05) lower in bottled water banned versus allowed facilities. This significant difference (p<0.05) was also reflected in the proportions of sales dollars for each category with 80% Do Not Sell and 14% Sell Most where bottled water was allowed compared to 91% Do Not Sell and 0% Sell Most in those facilities with a ban. Study 2: Guideline Implementation Factors and Changes in Facility Food Environment A breakdown of indicators that informed ratings for each guideline implementation factor and examples corresponding to higher ratings were provided. QCA Results QCA findings indicated that configurations with implementation factor ratings for each of Mobilization, Context and Policy indicated that higher levels were necessary to effect positive change in healthfulness outcomes. While high (5) ratings of each factor invariably resulted in positive change, there were various factor combinations of high (5), moderately-high (4) and moderate (3) factor ratings that were sufficient. Overall, somewhat higher ratings for Mobilization than the other two factors emerged in all successful configurations. Regression Analysis Results For Vending Beverages and Snacks, multiple regression analysis indicated that the three factors in the model: Mobilization, Context, and Facility-level Policy, were each significantly associated with a decrease in the proportion of Do Not Sell products. No significant associations with guideline implementation factors were found for beverage and snack proportions of Do Not Sell items within concessions nor for rNEMS-R Fast Summary scores. Study 3: EPL CBI Multiple-case Evaluation Framed by CFIR The facilities that emerged as ‘More’ (n=2) and ‘Less’ Successful (n=2) in improving the healthfulness of food offerings were, in each case, from British Columbia and Alberta. Each had made some positive changes across the multiple outcomes. Comparing and contrasting the More and Less Successful facilities across 49 constructs and sub-constructs of CFIR [1], 24 were distinguishing, 23 were not distinguishing and two were mixed. In particular, the More Successful facilities stood out for leveraging partnerships with local public health Registered Dietitians (Relational Connections, Implementation Facilitators), navigating resistance to nutrition guidelines and pushing for change (Tension for Change), accessing resources and utilizing EPL provincial coordinator support (Communication and Access to Knowledge & Information) and taking action toward improving healthfulness of the facility food environment (Planning, Tailoring Strategies, Engaging, Doing). CONCLUSIONS BY STUDY Study 1: Ontario Recreation and Sport Facility Food Environment In the absence of provincial nutrition policy/guidelines, most food and beverage offerings in participating facilities in Ontario were energy-dense and nutrient-poor, a finding mirrored in vending sales. Moreover, the healthfulness of the food environment was found to be vulnerable to unintended consequences of municipal-level policy. In jurisdictions that banned the sale of water in single-use plastic bottles offerings and sales of Do Not Sell beverages were proportionately higher than in facilities permitting bottled water. Moving forward, newer environmentally sustainable packaging options may provide a way for both health and sustainability goals to be met. Ironically, this finding demonstrated the power of mandated policy to alter food environments. Given that the food environment in facilities participating in the EPL study remained largely unhealthy even in provinces with voluntary nutrition guidelines [4], a mandated nutrition policy approach is recommended for Ontario moving forward. This would ensure that municipally-run facilities align with public health guidance by shifting the nutrition healthfulness of foods offered for sale. Ultimately, this would support the overall health of those enjoying recreation and sport facilities in Ontario. Study 2: Guideline Implementation Factors and Changes in Facility Food Environment The EPL trial found that recreation and sport facilities exposed to a capacity building intervention were better able to improve the availability of healthy foods in response to voluntary provincial nutrition guidelines than those without these supports [4]. This research aimed to determine the elements of the intervention that were most helpful. Higher ratings (moderate and above) in all three implementation factors (Mobilization, Context and Facility-level Policy) were necessary to support changes in recreation and sport facility food environments indicating implementation support approaches must include attention to all three to effect change. For Mobilization, ratings of moderately-high or high were necessary, suggesting that efforts supporting the number and intensity of mobilization activities such as monitoring and enforcement of existing food service contracts and food choice architecture approaches (e.g., positionality, cueing, changing default options) could have an impact on food environment healthfulness. Yet, Mobilization activities did not happen in isolation. Context and Policy were also necessary at moderate or moderately-high levels in combination with the higher Mobilization ratings and played a pivotal role in supporting mobilization activities; thus, attention to strategies focused on context elements (e.g., training, expertise, priority issues, structural barriers, partnerships) and facility-level policy development (e.g., food service contracts with healthfulness provisions) are critical. Study 3: EPL CBI Multiple-case Evaluation Framed by CFIR Use of the CFIR [1] to evaluate the CBI allowed identification of areas to direct future implementation support action to optimize nutrition guideline uptake in the municipally funded recreation and sport facility setting. The CBI training, support and resources of EPL enhanced capacity for nutrition guideline implementation and facilitated positive change in the healthfulness of foods offered. Change is difficult and some barriers were outside the control of facilities, yet all study facilities benefited to some degree from the suite of supports available and made some positive changes in enhancing the healthfulness of food environments. The More Successful facilities benefited particularly from partnerships and relationships. EPL provincial coordinators, public health dietitians, and support communities were among the relationships that facilitated their greater success. Effective engagement and ongoing communications were fundamental to those relationships. In order to foster meaningful change to the healthfulness of recreation and sport facility food environments, the current research points to the following recommendations for provinces or other jurisdictions instituting nutrition guidelines/policy: invest in dedicated and on-going expert implementation support; establish mechanisms for an on-going community of practice among those implementing guidelines; define clear steps in the progression towards full implementation of nutrition targets; develop comprehensive tools and resources to support revenue concerns and financial viability of the transition to healthier options for food service providers and facilities; create public messaging and setting-specific education campaigns to emphasize the value of healthy eating; and mandate provincial nutrition policy and assign accountability for implementation and monitoring within the regulatory framework. THESIS CONCLUSIONS AND CONTRIBUTIONS The research in this thesis has direct applicability to jurisdictions looking to implement recreation and sport facility food and nutrition guidelines/policy. Findings from the province of Ontario with Study 1 clearly identified that in the absence of policy the recreation and sport facility food environment is unhealthy. Moreover, findings also indicated that a lack of policy could make facilities vulnerable to local policies that do not consider public health impact, as was the case with the plastic bottled water ban. The EPL trial demonstrated that in the absence of capacity building supports, voluntary nutrition guidelines did little to change the healthfulness of recreation and sport facility food environments [4]. Studies 2 and 3 of this thesis research took advantage of the capacity building intervention of EPL in identifying and evaluating implementation supports that could make the most difference to nutrition guideline uptake. Study 2 demonstrated that a combination of factors were required at high to moderate levels; importantly, Mobilization required even higher levels than the factors Context or Facility-level Policy. This suggests that prioritizing such guideline mobilization strategies could improve implementation outcomes. In comparing most and least successful intervention facilities using the CFIR implementation framework, Study 3 identified points of action for implementation support. The structure provided with the use of CFIR increases transferability of the research to other settings. Jurisdictions increasingly recognize the paradox of recreation and sport facilities supporting active living yet providing unhealthy food and beverages. The lessons learned from this research can support meaningful change in recreation environments. There are many, including CBI facility leads involved in the current research, that feel that nutrition policy for recreation and sport facilities should be mandated and not limited to voluntary guidelines. Certainly, the findings of this thesis research indicate that strong supports for the process of policy of guideline implementation are needed for meaningful change. Ultimately, these changes could make recreation and sport facilities healthier food environments. Contribution This research contributes to current understanding of population-level policy implementation in community settings and can support policy planning, development, the implementation process and evaluation. The novel use of QCA analysis allowed a better understanding of the complexity and inter-relationship among factors influencing nutrition guideline implementation. The updated CFIR allowed identification of key factors influencing nutrition guideline implementation and extends our understanding of the application of implementation science in public health.
Keywords: food environments; food policy; nutrition policy; healthy eating; implementation science; recreation facilities; multiple case study